Transcutaneous Electrical Nerve Stimulation Effects on Neglect: A Visual-Evoked Potential Study - Pitzalis, Sabrina; Spinelli, Donatella; Vallar, Giuseppe; Di Russo, Francesco (Frontiers in Human Neuroscience, 2013)
We studied the effects of transcutaneous electrical nerve stimulation (TENS) in six right-brain-damaged patients with left unilateral spatial neglect (USN), using both standard clinical tests (reading, line and letter cancellation, and line bisection), and electrophysiological measures (steady-state visual evoked potentials, SSVEP). TENS was applied on left neck muscles for 15’, and measures were recorded before, immediately after, and 60’ after stimulation. Behavioral results showed that the stimulation temporarily improved the deficit in all patients. In cancellation tasks, omissions and performance asymmetries between the two hand-sides were reduced, as well as the rightward deviation in line bisection. Before TENS, SSVEP average latency to stimuli displayed in the left visual half-field [LVF, (160 ms)] was remarkably longer than to stimuli shown in the right visual half-field [RVF, (120 ms)]. Immediately after TENS, latency to LVF stimuli was 130 ms; one hour after stimulation the effect of TENS faded, with latency returning to baseline. TENS similarly affected also the latency SSVEP of twelve healthy participants, and their line bisection performance, with effects smaller in size. The present study, first, replicates evidence concerning the positive behavioral effects of TENS on the manifestations of left USN in right-brain-damaged patients; second, it shows putatively related electrophysiological effects on the SSVEP latency. These behavioral and novel electrophysiological results are discussed in terms of specific directional effects of left somatosensory stimulation on egocentric coordinates, which in USN patients are displaced towards the side of the cerebral lesion. Showing that VEP latency is modulated by proprioceptive stimulation, we provide electrophysiological evidence to the effect that TENS may improve some manifestations of USN, with implications for its rehabilitation.